Commentary on "Fall prevention for people with learning disabilities: key points and recommendations for practitioners and researchers". Issue 2 (3rd April 2018) - Freiberger, Ellen
Abstract : Purpose: Age-related processes are marked by physiological, psychological and social decline, threatening health, quality of life, functional status and the mobility of individuals. As the impact of demographic change also begins to affect persons with intellectual disabilities (ID), issues and needs regarding the aging process are slowly entering the field of ID research. The paper aims to discuss these issues. Design/methodology/approach: In the population of older people with ID, important, age-related events such as falls have prompted increasing research. Falls may lead to several negative health outcomes, require that an individual receives higher levels of care sometimes including hospitalisation and, in the worst case, hasten death. Falls also lead to psychological consequences such as fear of falling which fuels a vicious circle in which older persons afraid of falling reduce their physical activity, in turn hastening their functional decline. Findings: Fall prevention in persons with ID is just evolving and further research is clearly necessary. This research can draw on the existing evidence from other fall prevention areas, especially the work carried out with the general older population. Originality/value: As stated by Finlayson, a useful next step would be the development of a consensus on the definitions and methodology that should underpin future fall prevention research with persons with ID.